PREPARATION AND CHARACTERIZATION OF HYDROXYAPATITE BY CHEMICAL TREATMENT - Oyewumi-Musa , Rukayat Titilayo; Bello, M. O.; Abdus-Salam , Nasiru; Olabode , Sururat Olaitan (FUDMA JOURNAL OF SCIENCES, 2023)
Hydroxyapatite powder (HA) was prepared using the chemical precipitation method using diammonium hydrogen phosphate and calcium nitrate tetrahydrate as the starting materials. The solution was kept stirring for 24hrs at room temperature, white precipitates were dried and calcined at 1000ºC and 1200ºC for 4hrs. The powder sample was characterized by scanning electron microscopy (SEM), Fourier infrared spectroscopy (FTIR), X-ray diffraction (XRD), Elemental dispersive X-ray (EDX). The results showed that obtained HA powders were greatly influenced by synthetic conditions. SEM shows the morphology of crystals structure, large pores sizes were observed at 50µm and 100µm. The FTIR shows the presence of CO32-  at  1390 cm-1 and 1384 cm-1 which may be due to the adsorption of atmospheric CO2  on the surface of HA. PO42- was observed at 1046 cm-1 and 1092 cm-1. The EDX shows the presence of C, O, Na, Mg, Al, P, Ca. The histogram of EDX revealed oxygen carbon, phosphorus, and calcium as the major elements, sodium, magnesium, and aluminum were also present.
Keywords: Hydroxyapatite; chemical treatment; calcination temperature; characterization